2005
DOI: 10.1016/j.neuropharm.2005.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of two major Fragile X Syndrome mouse model phenotypes by the mGluR5 antagonist MPEP

Abstract: Fragile X Syndrome is the most common form of inherited mental retardation worldwide. A Fragile X mouse model, fmr1(tm1Cgr), with a disruption in the X-linked Fmr1 gene, has three substantial deficits observed in several strains: (1) sensitivity to audiogenic seizures (AGS), (2) tendency to spend significantly more time in the center of an open field, and (3) enlarged testes. Alterations in metabotropic glutamate receptor group I signaling were previously identified in the fmr1(tm1Cgr) mouse. In this study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
449
2
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 486 publications
(483 citation statements)
references
References 52 publications
30
449
2
2
Order By: Relevance
“…Remarkably, they found that audiogenic seizure susceptibility, increased basal protein synthesis, dendritic spine density and increased body weight were all rescued in Fmr1/mGluR5 double mutant mice. Subsequent studies have further validated the theory by pharmacologically rescuing audiogenic seizure, hyperactivity and dendritic spine morphology in Fmr1 knockout mice using the mGluR5 antagonist MPEP (Yan et al, 2005;de Vrij et al, 2008). Overall, the use of the mouse model and other models such as the drosophila and zebrafish models of FXS has led to increasing evidence of defective excitatory neurotransmission in FXS.…”
Section: The Mouse Model and Molecular Mechanisms Of Fragile X Syndromementioning
confidence: 96%
See 1 more Smart Citation
“…Remarkably, they found that audiogenic seizure susceptibility, increased basal protein synthesis, dendritic spine density and increased body weight were all rescued in Fmr1/mGluR5 double mutant mice. Subsequent studies have further validated the theory by pharmacologically rescuing audiogenic seizure, hyperactivity and dendritic spine morphology in Fmr1 knockout mice using the mGluR5 antagonist MPEP (Yan et al, 2005;de Vrij et al, 2008). Overall, the use of the mouse model and other models such as the drosophila and zebrafish models of FXS has led to increasing evidence of defective excitatory neurotransmission in FXS.…”
Section: The Mouse Model and Molecular Mechanisms Of Fragile X Syndromementioning
confidence: 96%
“…However, as opposed to the spontaneous seizures observed in FXS patients, seizures in Fmr1 knockout mice are specifically triggered by auditory stimuli (Musumeci et al, 2000;Chen and Toth, 2001). Seizure incidence in knockout mice have been shown peak in the third week of postnatal life (Yan et al, 2005). Finally, several independent studies have shown knockout mice to be hyperactive in the open field test (Bakker et al, 1994;Kooy et al, 1996;Mineur et al, 2002).…”
Section: The Mouse Model and Molecular Mechanisms Of Fragile X Syndromementioning
confidence: 99%
“…Thus, another issue that impacts clinical trial design will be age, as we would expect a priori the best outcome with early intervention. However, based on several animal studies (Aschrafi et al, 2005;McBride et al, 2005;Yan et al, 2005), we remain optimistic that significant benefit could be observed in some functional domains even if treatments were begun in adults.…”
Section: Synaptic Protein Synthesis and Brain Functionmentioning
confidence: 99%
“…Interestingly, there is now an mGluR theory of Fragile X syndrome, which hypothesizes that lack of the fragile X mental retardation protein (FMRP) causes a hyperactive response to mGlu5 receptor activation (Bear, 2005), possibly accounting for many of the symptoms of Fragile X syndrome, including the audiogenic seizures Yan et al, 2005). The pilocarpine-induced seizures, which were also sensitive to group I mGluR antagonists (Smolders et al, 2004), may share some of the same pathways as seizures induced by overly stimulating group I mGluR.…”
Section: Group I Mglur and Epileptiform Activitymentioning
confidence: 99%
“…Group I metabotropic glutamate receptor (mGluR) activation has been implicated as a mediator of epileptiform activity in several different models both in vitro (Arvanov et al, 1995;Burke and Hablitz, 1995;Taylor et al, 1995;Merlin and Wong, 1997;Martín et al, 2001;Lee et al, 2002) and in vivo (Tizzano et al, 1995;Camón et al, 1998;Thomsen and Dalby, 1998;Chapman et al, 1999;Chapman et al, 2000;Smolders et al, 2004;Yan et al 2005). In some of these models group I mGluR antagonists block the emergence of the epileptiform activity but do not block established epileptiform activity (Arvanov et al, 1995;Martín et al, 2001).…”
Section: Introductionmentioning
confidence: 99%